1983
DOI: 10.2307/3281359
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Poly A(+) RNA from Schistosoma mansoni and Immunoprecipitation of Its In vitro Translation Products

Abstract: Total RNA was extracted from S. mansoni by homogenization in 4 M guanidine thiocyanate followed by centrifugation through cesium chloride. Poly A(+) RNA was isolated by oligo(dT)-cellulose chromatography. The recovered poly A(+) RNA was subsequently shown to stimulate protein synthesis in a cell-free, rabbit reticulocyte system. Among the translation products were polypeptides with molecular weights of 18, 20, 26, 39, 42, and 50 kilodaltons that were recognized by rabbit anti-schistosome-denuded body IgG. Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Immunologically, differentiation ofparasite stages has been demonstrated using monoclonal antibodies developed against stage-specific proteins (24)(25)(26)(27). Recently, immunoprecipitation of in vitro translation products of S. mansoni mRNA using polyclonal antisera suggested that there are several adult worm-and schistosomula-specific polypeptides (28)(29)(30)(31)(32). Previous reports concerning cloning of S. mansoni antigens (33,34) did not describe RNA analyses which would have allowed comparisons to the cDNAs described in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…Immunologically, differentiation ofparasite stages has been demonstrated using monoclonal antibodies developed against stage-specific proteins (24)(25)(26)(27). Recently, immunoprecipitation of in vitro translation products of S. mansoni mRNA using polyclonal antisera suggested that there are several adult worm-and schistosomula-specific polypeptides (28)(29)(30)(31)(32). Previous reports concerning cloning of S. mansoni antigens (33,34) did not describe RNA analyses which would have allowed comparisons to the cDNAs described in the present study.…”
Section: Discussionmentioning
confidence: 66%